1994
DOI: 10.1159/000292446
|View full text |Cite
|
Sign up to set email alerts
|

Tubal Anastomosis in the Rat Using the Tissue Adhesive Cyanoacrylate (Histoacryl®)

Abstract: n-Butyl-2-cyanoacrylate (Histoacryl®) is said to be as effective as microsurgery for tubal anastomosis. In a prospective controlled study at the regional teaching hospital research laboratories, 40 female laboratory rats underwent laparotomy, with ligation of the uterine horns, and reanastomosis by microsurgery or cyanoacrylate tissue adhesive. Main outcome measures were patency of uterine horns following anastomosis, histologic examination of anastomotic sites and pregnancy rate following anastomosis by each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Haj N et al, retrospectively evaluated major reasons for the request for reversal which were a loss of children 50%, remarriage 27%, 10%. 9 Holst et al, studied comparison between microsurgical and micro laser techniques and concluded that the carbon dioxide laser's advantages (precision, homeostasis and the ability to preserve more normal reproductive tissue), although technically beneficial in performing microsurgical tubal reanastomosis, may not prove to be superior to conventional microsurgical technique as pregnancy rates are compared. Additional long-term studies are needed as more experience is gained to further delineate the role of the carbon dioxide laser for microsurgical tubal reanastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Haj N et al, retrospectively evaluated major reasons for the request for reversal which were a loss of children 50%, remarriage 27%, 10%. 9 Holst et al, studied comparison between microsurgical and micro laser techniques and concluded that the carbon dioxide laser's advantages (precision, homeostasis and the ability to preserve more normal reproductive tissue), although technically beneficial in performing microsurgical tubal reanastomosis, may not prove to be superior to conventional microsurgical technique as pregnancy rates are compared. Additional long-term studies are needed as more experience is gained to further delineate the role of the carbon dioxide laser for microsurgical tubal reanastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…it was seen that histologically that there were less foreign body granulomas. [ 5 ] Takenaka et al . clearly showed that cyanoacrylate anastomosis prevents anastomotic neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cyanoacrylate for anastomosis of vessels, the urogenital tract, and bowel have been reported in different experimental models ranging from rat to rabbits, and dogs and monkeys, with varying outcomes. [ 5 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings, various techniques with different surgical materials have been studied. Fibrin glue [9 -12] and cyanoacrylate [13,14] were found to be as effective as standard microsurgical anastomosis with suture materials. Autologous fibrin was associated with superior results compared to heterologous fibrin and conventional sutures [15,16].…”
Section: Discussionmentioning
confidence: 99%